Sounds of Lengilo based on the Swadesh List - Nur Ardini, Jian Abdullah; Hamidah, Abdul Wahab; Ting, Su Hie (Asian Scholars Network (ASNet), 2024)
The Lengilo is a small indigenous group who live in northern Sarawak and Malinau on Kalimantan Island of the Republic of Indonesia. They generally identify themselves as Lun Bawang in Sarawak and Lun Dayeh in Indonesia because of assimilation into these larger speech communities. This preliminary study examines phonetic aspects of the Lengilo language, focussing on vowels, consonants and diphthongs. To collect the data, a Swadesh list of 100 words was used. The informant interviewed was an 80-year-old native speaker of Lengilo. The results show that the Lengilo language has six types of consonants, three types of vowels and diphthongs. The six consonants are plosive, nasal, fricative, trill, lateral, and partial vowel. The Lengilo consonants do not occupy all the initial, middle and final positions of words. For example, velar plosive [g], alveolar fricative [s], glottal fricative [h], and lateral-alveolar [l]. The eight vowels in Lengilo are narrow front vowel [i], semi-narrow front vowels [e], semi-wide front vowels [ɛ], wide front vowels [a], semi-wide middle vowel [ə], narrow back vowel [u], semi-narrow back vowel [o], and semi-wide back vowel [ͻ]. The three types of diphthongs in Lengilo are [ai], [ui] and [oi]. The diphthong [ai] appears to be more productive than the diphthong [ui] and [oi] which are quite limited in number. The initial description of the Lengilo language is important for comparison with languages of indigenous groups in the Lun Bawang category.